Cinema and colour : the saturated image - Coates, Paul, 1953- (British Film Institute, 2011)
This is a critical study of the use of colour in cinema. Paul Coates unpacks the use of colour in a diverse range of films that deliberately exploit the different cultural meanings, symbolism and associations of colour, such as All that Heaven Allows, The Wizard of Oz, Three Colours and The Lives of Others, and many more.